Modeling Spatial Areas Prone to Sumatran Elephant (Elephas maximus sumatranus) Conflicts Around Bukit Tigapuluh National Park - Gilang Muhammad Dzaki; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Bukit Tigapuluh National Park (TNBT) is one of the national parks located on the island of Sumatra, known for its diverse protected fauna and flora, including the Sumatran Elephant. The surge in human activities such as poaching, forest fragmentation, and habitat destruction has led to an increasing potential for conflict between elephants and humans in the vicinity of TNBT. This study analyzes the potential distribution of conflicts between Sumatran elephants and humans around TNBT using the Maximum Entropy application, with conflict point data and environmental variables as references. The output of this research aims to analyze which environmental variables significantly contribute to Sumatran elephant and human conflicts (KGM) based on their distance from the conflict points. According to the modeling results, the environmental variables with significant contributions are forest edges and plantation areas, accounting for 48.1% and 24.8%, respectively, of the conflicts involving Sumatran elephants around TNBT. Tebo Regency is identified as an area highly prone to KGM around TNBT, with a total potential high-risk area covering approximately 46,685 hectares.